2021
DOI: 10.1007/s41027-021-00333-x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts and Strategies Behind COVID-19-Induced Economic Crisis: Evidence from Informal Economy

Abstract: The COVID-19 pandemic has put pressure on the informal sector, especially in developing countries. Regarding the case study found in Yogyakarta Special Region (Indonesia), this research focuses on workers in the informal sector with the following objectives: (1) to assess the impacts of COVID-19 pandemic on informal workers’ conditions, (2) to identify their strategies for surviving the crisis, and (3) to analyze the existing social safety net to support their livelihood. This study surveyed 218 respondents wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Thus, it is shown that workers mostly targeted informal entrepreneurship as a transition step to a permanent job or formal entrepreneurial activity. This finding aligns with that of Todaro and Stephen (2012) as well as with that of Pitoyo et al (2021), who noted that it is relatively easy to access the informal sector because it requires lower capital and fewer skills than the formal sector. In addition, Meng (2001) found that informal entrepreneurs possibly have a higher income than that gained from other activities within the formal or informal sectors in China.…”
Section: The Dynamics Of Main Employment Statussupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, it is shown that workers mostly targeted informal entrepreneurship as a transition step to a permanent job or formal entrepreneurial activity. This finding aligns with that of Todaro and Stephen (2012) as well as with that of Pitoyo et al (2021), who noted that it is relatively easy to access the informal sector because it requires lower capital and fewer skills than the formal sector. In addition, Meng (2001) found that informal entrepreneurs possibly have a higher income than that gained from other activities within the formal or informal sectors in China.…”
Section: The Dynamics Of Main Employment Statussupporting
confidence: 91%
“…Earlier studies have looked at mobility across sectors, regions, and locations (Calì et al, 2019;Kataoka, 2019) but have not provided estimates based on formality level. Second, we study the nexus between socio-demographic variables and labor mobility aimed at identifying sectors where policy efforts can bear fruit in supporting formality and identifying vulnerable groups (or slow movers) toward formality who may require additional policy support (Pitoyo, Aditya, Amri, & Rokhim, 2021). Third, we test whether improving skills development and training may help to increase mobility toward formal activities and increase permanence in formal employment.…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic caused workers' conditions to fall into the worst condition, 2.52% of workers experienced layoffs and 22.74% did not work, and 70.53% of the population had low incomes of less than IDR 1,800,000 who had become the most affected ones by the COVID-19 pandemic [2]. A preliminary study conducted in Indonesia also proved that the pandemic crisis disrupted the incomes of most informal workers [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Urban informal sector has been considered as the resting place where the urban in-migrants work until they find a formal sector job (Selod & Shilpi, 2021;Tran et al, 2022;Szaboova et al, 2022). But increasing number of studies in recent years has repeatedly shown an alternative role of urban informal sector (Acharya et al, 2009;Pitoyo et al, 2021). Rural-urban migration has inherent linkages to agricultural development (Mianabadi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%